The Penggunaan Pupuk Hayati Endomikoriza untuk Meningkatkan Efisiensi Pemupukan NPK pada Jagung Manis - Suwarto, Suwarto; Rahmad Suhartanto, Mohamad (Jurnal Hortikultura Indonesia (JHI), 2025)
Nitrogen (N), phosphorus (P), and potassium (K) nutrients are essential for sweet corn growth and yield. N, P, and K fertilizer is increasingly limited and expensive, so it should be an efficient application. Endomycorrhiza is a mycorrhiza that is symbiotic with roots, forming a hyphae network that expands the root surface to absorb nutrients.  The objective of this research was to study the role of Endomycorrhiza to the efficiency of N, P, and K fertilization. There were six levels: without fertilization, fertilization of 1.00 dose of Standard NPK, 1.00 dose of Standard NPK+Endomycorrhiza, 0.75 dose of Standard NPK+Endomycorrhiza, 0.50 dose of Standard NPK+Endomycorrhiza, and 0.25 dose of Standard NPK+Endomycorrhiza. Standard NPK is 135 kg N, 72 kg P2O5, and 120 kg K2O per hectare. The dose of Endomycorrhizal biofertilizer (2.1 x 103 CFU g-1 active mycorrhizal propagules) was 800 kg per hectare. The treatments were repeated 4 times. The number of leaves at 8 weeks after planting without fertilization was the least (11.8 leaves), which were fertilized with 1.00, 0.75, 0.50, and 0.25 doses of Standard NPK+Endomycorrhizae were more (average 13.7 leaves) than 1.0 dose of Standard NPK without mycorrhizae (12.9 leaves). The yield of husked cobs from 1.00, 0.75, and 0.50 doses of Standard NPK+Endomycorrhizae were similar and higher (average 5.44 tons ha-1) than 1.00 dose of Standard NPK without Endomycorrhizae (4.72 tons ha-1). The Endomycorrhiza biofertilizer could save 50% of the standard NPK dose with 11.2% higher results.  Keywords: corn cob weight, hyphae, mycorrhiza, propagules, symbiosis